Retention characteristics in Bi3.25La0.75Ti3O12 thin films prepared by the polymeric precursor method - Simoes, A. Z.; Ramirez, M. A.; Perruci, N. A.; Riccardi, C. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2005)
Ferroelectric Bi3.25La0.75Ti3O12 (BLT) thin films were deposited on Pt/Ti/SiO2/Si substrates by the polymeric precursor method. The films present c-axis preferred orientation after annealing at 700 degrees C for 2 h in conventional furnace. All the capacitors showed good polarization fatigue characteristics at least up to 1x10(10) bipolar pulse cycles and excellent retention properties up to 1x10(4) s. We found that the polarization loss is insignificant with five write/read voltages at a waiting time of 10 000 S. Independently of the applied electric field the retained switchable polarization approached a nearly steady-state value after a retention time of 10 s. (C) 2005 American Institute of Physics.